Respuesta :

Answer:

Step-by-step explanation:

[tex]cot(\frac{\pi }{2} -\theta)=tan \theta=-0.87[/tex]

or second method

[tex]\cot(\frac{\pi }{2} -\theta)=\frac{1}{\tan(\frac{\pi }{2} -\theta)} =\frac{1}{\frac{\tan\frac{\pi }{2} -\tan \theta}{1+\tan \frac{\pi }{2 } \tan \theta} } =\frac{1+\tan\frac{\pi }{2} \tan \theta}{\tan\frac{\pi }{2} -\tan \theta} \\(divide~the~numerator~and~denominator~by~\tan\frac{\pi }{2} )[/tex]

[tex]=\frac{\cot\frac{\pi }{2} +\tan\theta}{1-\cot\frac{\pi }{2} \tan\theta} \\=\frac{0+\tan \theta }{1-0*\tan\theta} \\=\tan \theta\\=-0.87[/tex]

ACCESS MORE